تطوير منهجية لفحص السلامة المرورية على الطرق الريفية (قطاع من طريق طرطوس - صافيتا) - Ranaa Darwish Ahmad; Darin Yousef (Tishreen University, 2019)
تطوير منهجية لفحص السلامة المرورية على الطرق الريفية (قطاع من طريق طرطوس - صافيتا) رناء درويش أحمد دارين يوسف يهدف فحص السلامة المرورية على الطرق الريفية إلى إيجاد النواقص والعيوب الموجودة على هذه الطرق إن كانت أخطاء تصميمية أو أخطاء ناتجة عن وضع الطريق موضع الخدمة, ويعد طريق طرطوس - صافيتا من الطرق الريفية بحارتين باتجاهين من الصنف الأول, وقد تمت دراسة 5km منه على جزأين, الجزء الأول دراسة 2km من الطريق حيث تم التقاط صور وأخذ القياسات للطريق, تمت دراسة عرض الطريق وعرض البانكيت وجوانب الطريق وظروف الرؤية والتلاؤم بين العناصر الأفقية و الشاقولية للطريق والتصريف والتقاطعات وحد السرعة وإمكانية التجاوز والشاخصات المرورية وعلامات الطريق والمشاة ووسائل النقل العام كل 100m وإعداد تقارير الفحص, التي تتضمن الصور مع وصف للصورة وذكر للعيوب الموجودة وإجراءات التحسين المقترحة, والجزء الثاني تمت دراسة 3km من الطريق, ولكن كل 50m, تم إعداد 81 تقرير, الدراسة تمت بالاعتماد على بيانات الحوادث بين عامي 2014 -2016, وقد أنجزت النتائج بعد جمع البيانات والقيادة على الطريق, وبعد المراقبة والمناقشة. وتم اقتراح مجموعة من الإجراءات لتحسين السلامة المرورية على القطاع المدروس. Road safety inspection on rural roads aims to find deficiencies and shortcomings existing on these  roads whether they were design errors or errors caused by putting the road in service. Tartous - Safita road is considered one of the rural roads with two lanes and two directions from the first classification. A distance 5km of  the road was studied In two sections. In the first part, 2km of the road was studied where photos and road measurements were taken; the road width, the bankit width, the road sides, visibility conditions, compatibility between the horizontal and the vertical elements of the road, drainage, intersections, speed limits, passing ability, the traffic signs, pedestrian and public transport and the road markers were studied every 100m and inspection reports were prepared. These reports contain photos with  descriptions and mention the existing deficiencies and proposed improvement procedures. The second part, 3km of the road was studied but every 50m, 81 reports were prepared. The study based on the accidents data  between 2014 - 2016, and the results were got after collecting the data and driving on the road, after  look out and discussion. A list of procedures was suggested to improve the road safety on the studied section.